Manure injection and rye double cropping increased nutrient recovery and forage production. (24th April 2020) - Binder, Jonathan M.; Karsten, Heather D.; Beegle, Doug B.; Dell, Curtis J.
Abstract: Double cropping forage cereal rye ( Secale cereale L.) with corn ( Zea mays L.) and injecting liquid dairy cow ( Bos taurus L.) manure in the fall may increase manure nutrient utilization and total forage production. Although potentially economically and environmentally beneficial, these practices have not been widely adopted by Northeastern U.S. farmers. This 2‐yr full‐factorial experiment conducted in Pennsylvania quantified the effects of (a) rye management (RyeM; early terminated cover crop, CC vs. double crop harvested approximately 1 wk later, DC) and (b) manure application method (ManM; unincorporated broadcasted manure, BM vs. shallow disk injected manure, IM) on rye biomass, rye apparent manure nitrogen and phosphorus recovery (ANR and APR, respectively), subsequent corn silage yield, and total forage production (DC + summer corn silage) and the effect of ManM on DC forage nutritive value. Double cropping increased rye biomass 143%, ANR 119%, APR 126%, and total forage production 29–44% compared to CC. While IM did not increase net returns on rye silage production compared to BM, IM improved rye forage nutritive value by increasing ANR by 84%, rye crude protein by 29%, net energy of lactation by 10%, and reduced neutral detergent fiber (NDF) by 10%. Injecting manure also increased summer corn yield 21% and total forage 13% when rye was harvested as DC compared to DC with BM. Farmers adopting DC can increase total forage production and nutrient recovery and, when combined with IM, forage production and rye quality can potentially be improved.